Potentials of Camphor, Basil, Jujube, Henna and Pomegranate for Future Research - Othman, Muhammad Remy; Ahmad, Khadher; Mohd Yusoff, Mohd Yakub @ Zulkifli; Awang, Khalijah; Md. Ariffin, Mohd Farhan; Safie, Shafiza (Online Journal of Research in Islamic Studies, 2021)
Flora is nature’s valuable treasure. The importance of flora in preserving the ecosystem is undeniable. Furthermore, there are several plants that have been mentioned in the Quran and hadiths. Some of them are camphor, basil, jujube, henna and pomegranate. The question is what are the characteristics of each plants mentioned above for them to have been placed in the religious texts? Thus, this research focusses on the potential scientific elements present in the plants to investigate its specialties. Based on the literature reviewed, it is found that previous researchs on camphor, basil, jujube, henna and pomegranate proved that each of the plants mentioned contains its own benefits. Hopefully, this article will open doors to further research that will bring profitable results for Malaysia.